OC-006 Safety And Efficacy Of Low Dose Azathioprine And Allopurinol Co-therapy: A Large Single Centre Experience. (9th June 2014) - Stamoulos, P; Stournaras, E; Bull, C; Cowan, M; Mackenzie, G; Stenner, J; Coulthard, S; Ansari, A
Abstract : Introduction: The effectiveness of full dose azathioprine (FDA) for inflammatory bowel disease (IBD) has been questioned in recent scientific literature. A popular strategy to improve its outcomes recommends the use of low dose azathioprine with allopurinol co-therapy (LDAA) for patients profiled as "hypermethylators" (30% of non-responders). The aim of this study was to determine the safety and efficacy of LDAA without using thiopurine metabolite (TM) profiling. Methods: Records of IBD patients treated with LDAA were retrospectively analysed. Patients who had poor response and/or side-effects to FDA were offered LDAA by all Consultants whilst a single IBD physician also offered LDAA to thiopurine-naïve patients. Azathioprine dose was reduced to 25% of the thiopurine methyl transferase (TPMT) adjusted dose (0.5 mg/kg for wild type and 0.25 mg/kg for heterozygotes) followed by conventional haematological monitoring. Non-adherence was assessed by TM measurements. Full response (FR) was defined as steroid free remission (Harvey Bradshaw index ≤3, Truelove-Witts normal) for greater than 3 months after a 3 month induction period for LDAA. Results: Of 300 LDAA patients, adequate data was available for 295 cases. Group 1 (G1) were treated 1 st line (n, 105) and Group 2 (G2) were switched from FDA to LDAA (n, 190). Overall, for both groups, there were 207 (70%) full responders (FR), 20 partial responders (PR) and 68 non-responders (NR). Full response rate was 78% in G1 and 66% in G2. The commonest indication for switching to LDAA was non-response to FDA (n, 118). Analysis of haematological indices revealed significant changes (p < 0.05) in erythrocyte sedimentation rate, white cell count and platelet count after therapy induction. Myelotoxicity occurred in 5 patients (all NR, WCC >2 and <3.5) and 12 patients had asymptomatic hepatotoxicity (ALT range: 100–700) which resolved by increasing allopurinol to 200 mg in 9 patients (all FR). Time on treatment: 208 patients took LDAA for more than twelve months with a median length of therapy of 24 months. Conclusion: Appropriately dosed LDAA therapy delivers a therapeutically effective dose of azathioprine without the need for dose escalation. It appears to be more effective, better tolerated and safer (less haematological disturbance) than FDA. These results will serve to allay the fear of toxicity of LDAA and question the need for thiopurine metabolite level profiling prior to using this apparently superior therapeutic approach. Disclosure of Interest: None Declared.